KARAKTERISASI KOMPOSIT FILM EDIBLE PEKTIN DAGING BUAH PALA (Myristica fragrans Houtt) DAN TAPIOKA [Characterization of Edible Film Composite Made of Pectin from Nutmeg Mesocarp and Tapioca] - Payung Layuk; Djagal W. M; Haryadi . (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2002)
The objective of the research was to investigate the properties of pectin derived from mesocarp of nutmeg (Mysristica fragrans Houtt) and edible film made from the pectin and added tapioca. Pectin was extracted from mesocarp of nutmeg using 0.5% of EDTA at pH 1.5-2, and temperature at 90°C for 1 hour. The first group of edible film was prepared using 1% (w/v) of pectin, 1.6% CaCl2, 1% glycerol and various concentration of tapioca (0-2%, w/v). Second group of edible film was prepared using 1% of pectin, 1.6 % CaCl2, 1% glycerol and 2% tapioca and various concentration of palmitic acid (0-0,08 w/v). Physical, mechanical and barrier properties of the films were examined and its capability to reduce weight loss of small pieces of apples during storage was also measured. The result showed that yield of isolated pectin was 20.73% (w/w) having methoxyl content 11.43%, and polygalacturonic acid of 79.47%. Proximate analysis showed that protein, ash and water content in the isolated pectin were 7.86, 3.03 and 7.60%, respectively. Characteristics of first group of film showed that the higher concentration of tapioca added resulted in the higher of tensile strength and thickness. Data of the second groups of films showed that addition of palmitic acid up to 0,08% has no effects on tensile strength, thickness, elongation and water vapour transmission rate (WVTR) of films. Small piece of apples coated or wrapped with edible film (1% pectin – 1,6% CaCl2-2% tapioca-1% glycerol and 0.04% palmitic acid) had lower weight loss and better colour than those of control during storage).